Islamisasi Ilmu sebagai Model Integrasi dalam Membangun Relasi antara Ilmu dan Agama (Tinjauan Historis-Filosofis) - Irawan, Vaesol Wahyu Eka (LP2M Sekolah Tinggi Islam Blambangan Banyuwangi, 2019)
Abstract: Islamization of knowledge emerged when the first world conference was held on Islamic education in Mecca on March 31 to April 8, 1977 with the theme,